Transdisciplinary Approach to Human Aging Research - Robiņa, Ineta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aging of elderly people in the transdiciplinary approaches has been described on the results of the analysis of the scientific literature. That thanks to the scientific achievements in different spheres the human life expectancy increases thus aging becomes an active participation process and due to the increase of the number of elderly people in the world a new branch of science – gerontology develops that turns its attention to researching the aging processes and the possibilities of lengthening the life expectancy; it includes three main research approaches – biological that deals with functional and morphological changes in human organ systems, psychological (changes in the sensory perception and mental processes) and sociological – human role and the changes of their interaction in the social structure. Aging is a regressive process, which is also influenced by negative and harmful factors that decrease the adaptation abilities of the organism. Gradually people reach a general status of inability. Thus the biological psychological and social aging is mutually closely connected. The authors has developed the theoretical framework on the studies of the aging theories.